Timbunan Sampah Organik dan Potensi Emisi Metana di Nusa Tenggara Barat - Krisna Wijaya; Taslim Sjah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The increasing generation of household organic waste has become a serious challenge in supporting low-carbon development in regions experiencing rapid population growth, such as West Nusa Tenggara Province (NTB). The low level of waste management causes most organic waste to end up in Final Disposal Sites (TPA), where it undergoes anaerobic decomposition and produces methane gas (CH₄), one of the Greenhouse Gases (GHGs) with a global warming potential 28–34 times higher than carbon dioxide (CO₂). This study aims to identify the magnitude of household organic waste generation, estimate methane (CH₄) emissions produced, and analyze its implications for regional low-carbon development. The method used is descriptive analysis with secondary data sources, using households as the main unit of analysis for organic waste generation. Data were obtained from Statistics Indonesia (BPS), the National Waste Management Information System (SIPSN-KLHK), NTB Low Carbon Development Planning documents (PRKBI), and the IPCC 2006 guidelines using the First Order Decay (FOD) approach. The results show that with a population of 5.73 million in NTB in 2025, household organic waste generation reaches approximately 769,489 tons/year with an estimated methane emission of ±38,474 tons CH₄/year or equivalent to ±1,077,272–1,308,116 tons CO₂e/year. The waste management rate of only 13.48% increases emissions risk from the waste sector, indicating that household organic waste management must be positioned as a strategic instrument in emission mitigation and in supporting low-carbon development in West Nusa Tenggara Province.